El problema del innatismo en Antonio Rosmini (parte I) - Franck, Juan F. (Sapientia, 2006)
The Nuovo saggio sull'origine delle idée, which contains Antonio Rosmini's (1797-1855) theory of knowledge, constituyes one of the most important works in modern philosophy, comparable to Leibniz' Nouvaux Essais and to Kant's Kritik der reinen Vernunft. Rosmini takes part in the modern discussion about the nature and origin of our ideas. His solution offers a truly original variant of the central core of innatism, both ancient and modern, which bears many consequences for the rest of philosophy. The first part of the present study analyses the process in which Rosmini's thought achieved maturity and the definite expression of the theory. Secondly, the main features of this theory are outlined. Apart from its novelty, the interest of Rosmini's theory of knowledge lies in its capacity to relate the ancient with the modern by means of a sharp sense of criticism, and in its capacity to shed light upon many modern philosophical problems.